Examining Gaps in Mathematics Achievement Among Racial-Ethnic Groups, 1972-1992 - Berends, Mark (RAND Corporation, 2005)
Examines trends in the mathematics scores of different racial-ethnic groups over time and analyzes how changes in family, school, and schooling measures help explain changes in the test score gaps. Although there were few positive changes between schools, the within-school experiences of black and Latino students changed for the better compared with white students when measured by student self-reported academic track placement.